2015
DOI: 10.1063/1.4907996
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive microcantilever aptasensor for ricin detection and kinetic analysis

Abstract: Up to now, there has been no report on target molecules detection by a piezoresistive microcantilever aptasensor. In order to evaluate the test performance and investigate the response dynamic characteristics of a piezoresistive microcantilever aptasensor, a novel method for ricin detection and kinetic analysis based on a piezoresistive microcantilever aptasensor was proposed, where ricin aptamer was immobilised on the microcantilever surface by biotin-avidin binding system. Results showed that the detection l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The system showed a detection limit of 4 nM, and the study results also demonstrated that the RNA aptamer can bind to the siderophore binding pocket of the protein. In 2015, Liu et al [ 158 ] modified a dynamic microcantilever with the biotin–antibiotin system to detect ricin protein. In 2018, the group of Agarwal [ 159 ] detected a heart-type fatty acid-binding protein (h-FABP) in a trace amount (100 ng/mL) by employing a piezoresistive SU-8/CB microcantilever platform for the first time.…”
Section: Application Of Genetic-probe-modified Cantilevermentioning
confidence: 99%
“…The system showed a detection limit of 4 nM, and the study results also demonstrated that the RNA aptamer can bind to the siderophore binding pocket of the protein. In 2015, Liu et al [ 158 ] modified a dynamic microcantilever with the biotin–antibiotin system to detect ricin protein. In 2018, the group of Agarwal [ 159 ] detected a heart-type fatty acid-binding protein (h-FABP) in a trace amount (100 ng/mL) by employing a piezoresistive SU-8/CB microcantilever platform for the first time.…”
Section: Application Of Genetic-probe-modified Cantilevermentioning
confidence: 99%
“…The relationship between the microcantilever response time and the ricin concentration is shown in Figure 9 c. The response time from injection to dynamic equilibrium were 2645 s, 3326 s, 4121 s, 4452 3, and 4875 s for the concentrations of ricin 10 ng/mL, 20 ng/mL, 40 ng/mL, 60 ng/mL and 100 ng/mL, respectively. The limiting factor for response time depend on a complicated dynamic process of the ricin aptamer and ricin [ 33 ]. At the same time, abrin, which is also a dimeric glycoprotein, was used as the target molecule to evaluate the specificity of the ricin aptamer sensor.…”
Section: Biological Detectionsmentioning
confidence: 99%
“…For the Bio MEMS and Applications, the investigations of composite vascular repair grafts via Micro-imprinting and electrospinning 22 and piezoresistive Micro cantilever aptasensor for ricin detection and kinetic analysis are reported. 23 Also, the design of a telemetry system based on wireless power transmission for physiological parameters monitoring is proposed. 24 Three papers are shown in Nano materials field, two of which are focused on diamond film: voltammetric and impedance behaviors of surface-treated Nano-crystalline diamond film electrodes 25 and the effects of hydrogen atoms on surface conductivity of diamond film.…”
mentioning
confidence: 99%